2017
DOI: 10.32674/jis.v7i2.385
|View full text |Cite
|
Sign up to set email alerts
|

Digital Journeys: A Perspective on Understanding the Digital Experiences of International Students

Abstract: The authors in this conceptual paper draw on the literature on information seeking behavior, social media use, and international student experiences to propose Digital Journeys as a framework which helps us understand the online behavior of international students. Here we theorize that the Digital Journey is the transition that individuals make online from relying on one digital bundle of information sources to a new bundle. This “new” digital bundle possibly can base in the new host country or internationally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 36 publications
3
35
0
Order By: Relevance
“…Importantly, several researchers have highlighted social networks as being important sources of information (Sin & Kim, 2013). More specifically, Chang and Gomes (2017a) identified that 'communities play a vital role in facilitating … [an individual's] … engagement with new [online] sites'. This article thus seeks to anchor the discussion of how international students engage with online information by exploring the breadth of student social networks, as an important source of information.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, several researchers have highlighted social networks as being important sources of information (Sin & Kim, 2013). More specifically, Chang and Gomes (2017a) identified that 'communities play a vital role in facilitating … [an individual's] … engagement with new [online] sites'. This article thus seeks to anchor the discussion of how international students engage with online information by exploring the breadth of student social networks, as an important source of information.…”
Section: Introductionmentioning
confidence: 99%
“…Literature on international students and their uses of digital media has predominantly focused on how they retrieve information across areas of study and everyday logistics (e.g. where to look for information regarding accommodation and health services) (Chang and Gomes, 2017). In their work on Chinese international students in Melbourne, Fran Martin and Fazal Rizvi (2014) argue that digital media create a ‘glocal’ experience for international students.…”
Section: Digital Media In Friendships Built On Migrant Experiencesmentioning
confidence: 99%
“…During the student's life in the host country, social media is also helpful in keeping them socially connected with people both in their host and home countries. Students usually tend to make online connections with co-national friends, international friends and domestic friends [23,24]. Thus, different studies have shown the impotence of social media on international students' life abroad, however, there are some important gaps in the literature which need to be covered, particularly with a consideration of certain host countries and students' nationalities.…”
Section: Literature Reviewmentioning
confidence: 99%